Analysis of building envelope for energy consumption and indoor comfort in a near-zero-energy building in Northwest China - Xiaofei Zhen; Shange Li; Jianming Peng; Zhouyang Zhao; Xu Zhang; Chuanxi Tan; Ruonan Jiao; Wenbing Wu (Results in Engineering)
Abstracts: This study investigates the influence of building envelopes on energy consumption and indoor comfort in a near-zero-energy building located in northwest China using experimental testing and TRNSYS/CFD simulations. The results indicate that optimized envelope designs, particularly those incorporating rock wool insulation and a suitable window-to-wall ratio, can significantly reduce energy consumption, especially during the heating season, while maintaining indoor thermal comfort. The building's annual heating energy consumption is 10.58 kWh/m²/year, which is below the threshold of 15 kWh/m²/year defined for nearly zero-energy buildings (NZEBs). Further optimization, such as increasing insulation thickness and enhancing renewable energy utilization, is suggested to achieve higher energy efficiency and fully meet the criteria for NZEBs. This study provides valuable insights into energy-efficient envelope design for cold climates and highlights the importance of selecting appropriate materials and configurations to achieve both energy savings and indoor comfort.